Exploring Chilean student perceptions of opportunity entrepreneurship - Corbett-Lagos, Karen; Muraro, Vinicius (Paper in innovation studies, 2025)
This study explores how Chilean university students perceive entrepreneurship, exploring whether they see it as an opportunity to address societal challenges or primarily as an enterprise creation. The research focuses on how these perceptions vary by gender in front of sociodemographic, academic, and institutional influential factors. Using a quantitative approach, we collected data from a sample of 973 students from different fields of study and conducted statistical analyses to determine the importance of factors that determine entrepreneurial attitudes. The results reveal that the majority of students see entrepreneurship as an opportunity to influence society and address social issues. Sociodemographic factors do not show statistical significance, suggesting that, within this specific population, they do not substantially alter the motivations for entrepreneurship. Although students may share similar views on the opportunity or business nature of entrepreneurship, the factors shaping this perception differ by gender. Among these factors, the value of active and engaged university support, especially in the form of experiential learning methodologies, in fostering opportunity driven entrepreneurship is highlighted. In contrast, resources such as infrastructure and institutional culture, while important, appear to play a more limited role. This research underscores the need for a holistic approach to entrepreneurship education, but with special attention to particular differences between the segments being served, integrating institutional support with hands-on learning methods to better cultivate an entrepreneurial culture to economic growth and mindset geared towards addressing societal problems.
Keywords: Entrepreneurship; Higher education; Opportunity-driven entrepreneurship; Gender disparities; Chile